PROSES LISTRIK DALAM TUBUH MANUSIA - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2016)
Bioelectromagnetism (sometimes equated with bioelectricity) refers to the electrical, magnetic or electromagnetic fields produced by living cells, tissues or organisms. Examples include the cell potential of cell membranes and the electric currents that flow in nerves and muscles, as a result of action potentials. It is not to be confused with bioelectromagnetics, which deals with the effect on life from external electromagnetism. Bioelectromagnetism involves the interaction of ions. Bioelectromagnetism is sometimes difficult to understand because of the differing types of bioelectricity, such as brainwaves, myoelectricity (e.g., heart-muscle phenomena), and other related subdivisions of the same general bioelectromagnetic phenomena. One such phenomenon is a brainwave, which neurophysiology studies, where bioelectromagnetic fluctuations of voltage between parts of the cerebral cortex are detectable with an electroencephalograph. This is primarily studied in the brain by way of electroencephalograms